Investigating European XBRL Filings: Hit or Miss? - Heichl, Veronika; Hirsch, Simon; Zvekan, Goran (Social Science Research Network, 2025)
Purpose The European Union has mandated that as of 1 January 2020, listed companies must file consolidated financial statements in the European Single Electronic Format (ESEF) using eXtensible Business Reporting Language (XBRL). This study assesses the effectiveness of Directive 2019/815, focusing on its objectives related to transparency, comparability, accessibility, and ease of analysis of ESEF filings. Design/methodology/approach The study employs ESEF filings from STOXX Europe 600 companies for the fiscal years 2021 and 2022. The transparency and comparability of statements are evaluated using Kruskal–Wallis tests to investigate variations by country, industry, and company size, followed by Dunn’s tests to identify variation drivers. The distribution and use of extensions are analysed through automated text processing to assess accessibility and ease of analysis. Findings Our findings suggest that the transparency and comparability of ESEF filings are constrained by significant variations. Moreover, crucial financial information remains partially inaccessible due to inconsistent application. We identify factors hindering accessibility and ease of analysis of ESEF filings, including the misuse of ESEF elements as extensions, the (dis)aggregation of elements, and the incorporation of domestic languages. Originality/value The study offers timely empirical evidence regarding the effectiveness of the ESEF directive in harmonising financial reporting. It can be reasonably concluded that the directive’s effectiveness is limited. ESEF presents challenges for stakeholders, particularly in terms of transparency, comparability, accessibility, and ease of analysis of reports. Regulators need to address these issues and potentially make adjustments to ensure harmonisation. <
Keywords: XBRL; ESEF; Financial Reporting; Extensions